2012
DOI: 10.1111/j.1432-2277.2011.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal function, efficacy and safety postconversion from twice- to once-daily tacrolimus in stable liver recipients: an open-label multicenter study

Abstract: Summary This multicenter, open‐label, phase III study assessed renal function, safety, and efficacy in stable adult liver transplant recipients converted from tacrolimus twice‐daily (BID) to once‐daily (QD). Patients received tacrolimus BID for 6 weeks before conversion to tacrolimus QD (1:1 [mg:mg] total daily dose basis) for 12 weeks. Primary endpoint: change in steady state creatinine clearance (CrCl) between treatment phases. Of 112 patients enrolled, 98 were converted to QD dosing (full analysis set [FAS]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
6
37
1
1
Order By: Relevance
“…Three studies reported that within-subject variability [percentage coefficient of variation (% CV)] in AUC 0-24 or C min decreased significantly following conversion from Prograf Ò to Advagraf Ò [28,35,43], while two studies could find no significant difference [31,45]. Conversion from Prograf Ò to Advagraf Ò resulted in a significant reduction in within-subject variability in tacrolimus AUC 0-24 from 14.1 to 10.9 % (but no reduction in C min ) in a study involving 40 stable kidney transplant recipients, assessed using five AUC values for each dosing regimen [28], and a reduction in tacrolimus C min from 14.0 to 8.5 % in a study involving 129 stable kidney transplant recipients [35].…”
Section: Xrmentioning
confidence: 97%
“…Three studies reported that within-subject variability [percentage coefficient of variation (% CV)] in AUC 0-24 or C min decreased significantly following conversion from Prograf Ò to Advagraf Ò [28,35,43], while two studies could find no significant difference [31,45]. Conversion from Prograf Ò to Advagraf Ò resulted in a significant reduction in within-subject variability in tacrolimus AUC 0-24 from 14.1 to 10.9 % (but no reduction in C min ) in a study involving 40 stable kidney transplant recipients, assessed using five AUC values for each dosing regimen [28], and a reduction in tacrolimus C min from 14.0 to 8.5 % in a study involving 129 stable kidney transplant recipients [35].…”
Section: Xrmentioning
confidence: 97%
“…The lower peak levels and reduced interpatient and intrapatient variability is observed with extended release tacrolimus after conversion from regular release tacrolimus in stable liver transplant recipients [10,11]. However, there still exists a significant intrapatient and interpatient variability in peak levels and area under curve (AUC) in de-novo transplant patients necessitating the need for frequent blood drug level monitoring [12].…”
Section: Pharmakokineticsmentioning
confidence: 99%
“…[2][3][4][5] These studies demonstrated that pharmacokinetics of twicedaily tacrolimus and the 2 formulations of once-daily tacrolimus are significantly different. Because no such data are available to date, the aim of the present study was to analyze the impact of conversion in daily practice from PR-Tac to ER-Tac among a large cohort of stable LT recipients, especially with regard to pharmacokinetics, safety, and cost.…”
Section: Introductionmentioning
confidence: 99%